MOLLUSCICIDAL AND LARVICIDAL ACTIVITIES OF Atriplex inflata AERIAL PARTS AGAINST THE MOLLUSK Galba truncatula, INTERMEDIATE HOST OF Fasciola hepatica - HAMED, Néjia; NJEH, Fatma; DAMAK, Mohamed; AYADI, Ali; MEZGHANI-JARRAYA, Raoudha; HAMMAMI, Hayet (Revista do Instituto de Medicina Tropical de São Paulo, 2015)
Fasciolosis is a widespread parasitosis of farm live-stock in many developing countries. For this reason, it is necessary to search for new substances against parasitic diseases caused by flukes. Indeed, a wide variety of terrestrial plants have been subjected to chemical and pharmacological screening in order to discover their potential for human medicinal use. The molluscicidal and larvicidal activities of Atriplex inflata were tested on Galba truncatula and Fasciola hepatica larval stages infecting this snail in Tunisia. Phytochemical tests were conducted on extracts in order to establish a meaningful relationship with molluscicidal and larvicidal activities. The molluscicidal activity was evaluated by subjecting snails to sample aqueous solutions. Accordingly, hexane, ethyl acetate, methanol and methanol-water (8:2, v-v) were used as extraction solvents. As a result, hexane and ethyl acetate extracts showed potent activity, according to the World Health Organization, giving LC50 = 7.59 mg/L and 6.69 mg/L for hexane extracts of leaves and fruits, respectively. Ethyl acetate extracts gave LC50 = 5.90 mg/L and 7.32 mg/L for leaves and fruits, successively. Molluscicidal activities of powders were less potent on snails, but active according to the World Health Organization. Hexane and ethyl acetate extracts from leaves and fruits gave potent larvicidal activities with a delay rate exceeding 45.50% (45.50- 98.92%). Phytochemical tests showed that these activities may be attributed to the presence of triterpenoids and/or sterols.